Effects of intradialytic exercise for advanced-age patients undergoing hemodialysis: A randomized controlled trial. - Hiroki Yabe (Public Library of Science (PLoS), 2021)
Previous reports have shown the benefits of intradialytic exercise to patients undergoing hemodialysis. However, most of those studies assessed the effects of exercise in middle-aged patients and little is known about advanced-age patients undergoing hemodialysis. Therefore, the present randomized controlled trial was performed to determine the effectiveness of exercise therapy in advanced-age patients undergoing hemodialysis. This non-blinded, randomized controlled parallel trial enrolled a total of 101 patients who were randomly assigned to intradialytic exercise (n = 51) or usual care (n = 50) groups. The training program included both resistance and aerobic exercises and was performed three times per week for 6 months. The aerobic exercise intensity was adjusted to a target Borg score of 13 for 20 minutes. Four types of resistance exercises were performed using elastic tubing, with three sets of 10 exercises performed at moderate intensity (13/20 on the Borg scale). The usual care group received standard care. Lower extremity muscle strength, Short Physical Performance Battery score, and 10-m walking speed were the outcomes and were evaluated before the hemodialysis session and after 6 months of training. There were statistically significant improvements in Short Physical Performance Battery score (effect size, 0.57; 95% confidence interval, 0.15‒1.95) in the exercise group relative to the control group. There were no statistically significant differences in lower extremity muscle strength or in the 10-m walking speed between the two groups. These findings suggest that 6 months of intradialytic training could improve physical function in older patients undergoing hemodialysis.